Ethics in the Qumran Community An Interdisciplinary Investigation - Tso, Marcus K.M (Mohr Siebeck, 2010)
Ethik in der Gemeinde von Qumran. Eine interdisziplinäre Studie.
PublicationDate: 20101109
Keywords: Second Temple -- Deas Sea Scrolls -- Qumran Community -- Religious Ethics -- Altes Testament -- Neues Testament -- Antike -- Array